Exploring Factors Shaping Consumer Decisions: A Qualitative Analysis of INK Helmet Purchases in Surabaya - Qoyyimah, Qoyyimah (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The INK helmet is a head safety device when driving. A helmet is a head protective device that is usually made of metal or other hard materials, such as Kevlar, resin fiber, or plastic. Motorcycle riders are required to use helmets, which is an important factor in supporting safe driving. Indonesia is an area with undisclosed weather. Rain fell suddenly in the morning, afternoon, and evening. When riding a motorbike in rainy conditions, the helmet will be exposed to rainwater. This research aims to know the principles of product diversity, product quality perception, price perception, and brand trust regarding purchasing decisions. The results of the research show that product diversity has an influence on purchasing decisions. Apart from that, purchasing decisions are also determined by perceptions of product quality. Meanwhile, price perception and brand trust influence the decision to purchase an INK helmet. Thus, the opinion in the findings of this research also shows that brand trust is an important precursor to both attitude and purchase loyalty, which are two different types of brand loyalty. Brand trust influences purchasing decisions.